2016
DOI: 10.4236/oalib.1103097
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malaria Positive Rapid Diagnostic Test and Antimalarial Treatment in Patients with Fevers in the Accident and Emergency Unit of Effia Nkwanta Regional Hospital, Western Region, Ghana

Abstract: Background: Rapid diagnostic test (RDT) is a simpler, easy to read malaria diagnostic test. It was introduced by the World Health Organization (WHO) to supplement the use of microscopy and can be used alone in areas where microscopy is unavailable. Its introduction was necessary to maintain the WHO test-based treatment protocol for malaria, as dependence of microscopy which is the gold standard is not possible in many areas in Sub-Saharan Africa which lack the wherewithal to run efficient laboratory services. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
3
0
0
Order By: Relevance
“…In this study, the prevalence of malaria was found to be 20.9%. This is consistent with a study conducted in Ghana on the prevalence of malaria-positive rapid diagnostic tests and antimalarial treatment which reported a 21.58% prevalence rate [ 8 ]. A similar study by Deku and colleagues in their retrospective study on malaria in the Western North region of Ghana reported, a slightly higher prevalence rate of 26.5% was reported [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the prevalence of malaria was found to be 20.9%. This is consistent with a study conducted in Ghana on the prevalence of malaria-positive rapid diagnostic tests and antimalarial treatment which reported a 21.58% prevalence rate [ 8 ]. A similar study by Deku and colleagues in their retrospective study on malaria in the Western North region of Ghana reported, a slightly higher prevalence rate of 26.5% was reported [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the prevalence of malaria was found to be 20.9%. This is consistent with a study conducted in Ghana on the prevalence of malaria-positive rapid diagnostic tests and antimalarial treatment which reported a 21.58% prevalence rate [12]. A similar study by Deku and colleagues in their retrospective study on malaria in the Western North region of Ghana reported, a slightly higher prevalence rate of 26.5% was reported [13].…”
Section: Prevalence Of Malaria Casessupporting
confidence: 89%
“…This concept is in line with the observations of this study where highest prevalence was recorded in children ≤ 10 years old than with the other age intervals. This supports the fact that children are still at risk of malaria despite the decreasing malaria burden in the zone [18,21,22]. Studies conducted elsewhere reported associations between malaria infection and the use of insecticide treated bed nets.…”
Section: Discussionsupporting
confidence: 70%